Pengaruh Beberapa Cara Penyiapan Media Tumbuh dan Dosis Pupuk Kandang Ayam Terhadap Pertumbuhan serta Produksi Bawang Dayak Di Banjarbaru - Indriani, Fazerina; Dewi, Indya; Darmawan, Arief Rakhmad Budi (Agroekotek View, 2023)
This study aims to determine whether the various methods of preparing growth media combined with chicken manure have an effect and provide an interaction with the growth and production of Dayak onions in Banjarbaru. September to February 2019 is the time this research conducted in garden of the agricultural faculty of Lambung Mangkurat University, Banjarbaru, South Kalimantan. In this study, a two-factor randomized block environment design (RBD) was used.Factor 1 How to prepare the growing media (m) which consists of 2 levels, namely (m1) = media processing with a hoe, (m2) = soil with a tractor. Factor 2 Dose of manure (k) there are 4 levels, namely (k0) = 0 kg, (k1) = 20 kg, (k2) = 30 kg, (k3) = 40 kg. Based on these two factors, 8 treatment combinations were obtained, each of which was repeated 3 times, in order to got 24 experiience units. Based on the research conducted, it showed that the combination of several treatments for the preparation of growth media and the application of chicken manure did not have a significant effect on all variables, but had an effect on the single factor.